Cotidiano da suspeita: etnia e criminalização na Bélle Époque amazonense - portugueses, índios, tapuios, cabocos e nordestinos, 1890 1920 - Santos Júnior, Paulo Marreiro dos (2011)
The research had the objective of investigating Manaus in the period of town planning and architectural transformation, found in the economy of the eraser, choosing Portuguese, Indians, tapuios, cabocos and Northeasterners as historical protagonists, while marginalized, considered suspects, dangerous to the effective order, opposed ethnic and social to the ideas of European habits, modernity, civility and progress. It was looked for to evidence a dynamic and multiple process, tense coexistence relationships with senses and glances on the elect protagonists. The form was to inquire the relationships between etnia and criminality, through theories and social and racial speeches, circulated and appropriate for the Press amazonense, authorities and writers' works, focusing in the chronicles policemen and emphasizing the vision of the society, or of the effective order, on the ethnic specificities. The research is justified for the contribution to the History under the theme of ethnic-social character to the light of the daily criminal, criticizing the imaginary hegemonic and the mystic of the nationalism of a Manaus of the Eraser is absent of marginalized social segments, disqualified by his/her race, without contrasts, without tensions, without poverty. Such taskwork was accomplished through a documental group that it was synthesized and filtrate, they were Codes, Ordinances, Messages of Government, literary registrations, and several journalistic matters, besides the one of criminal stamp, historical sources loaded of references cultural, racial and social, evidencing a disciplinary context and that it is imposed. With four chapters, there was the intention to analyze the context and to visualize the atmosphere of transformation of the city and of their inhabitants, these under the cultural and racial inclinations, by senses data to the Portuguese and the suspicions of social danger, tends as objectives of the Indian "order", tapuios, mestizos cabocos and Northeastern migrants